HD 89345: a bright oscillating star hosting a transiting warm Saturn-sized planet observed by K2 - Van Eylen, Vincent; Heeren, Paul (Arxiv, 2018)
We report the discovery and characterization of HD 89345b (K2-234b; EPIC 248777106b), a Saturn-sized planet orbiting a slightly evolved star. HD 89345 is a bright star = 9.3$ mag) observed by the K2 mission with one-minute time sampling. It exhibits solar-like oscillations. We conducted asteroseismology to determine the parameters of the star, finding the mass and radius to be $1.12^{+0.04}_{-0.01}~M_\odot$ and $1.657^{+0.020}_{-0.004}~R_\odot$, respectively. The star appears to have recently left the main sequence, based on the inferred age, $9.4^{+0.4}_{-1.3}~Gyr$, and the non-detection of mixed modes. The star hosts a "warm Saturn" = 11.8$~days, $R_p = 6.86 ± 0.14~R_\oplus$). Radial-velocity follow-up observations performed with the FIES, HARPS, and HARPS-N spectrographs show that the planet has a mass of $35.7 ± 3.3~M_\oplus$. The data also show that the planet's orbit is eccentric (
Gesehen am 01.02.2019